The Effectiveness of Easy English YouTube Channel to the EFL Students’ Vocabulary Mastery - Nurul Fadila Trijunianti; Ika Rama Suhandra; Afif Ikhwanul Muslimin (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2025)
This study investigated the effectiveness of the Easy English YouTube channel in improving EFL students’ vocabulary mastery at an Islamic junior high school in Indonesia. A quasi-experimental design was employed involving two classes selected from eight available classes. The experimental group received instruction using the Easy English YouTube channel, while the control group was taught using conventional methods. The participants consisted of 50 students. Vocabulary tests were administered as pre-tests and post-tests to measure students’ vocabulary mastery. The results showed that the experimental group’s mean score increased from 55.20 to 85.00, while the control group’s mean score increased from 52.40 to 75.20. An independent samples t-test revealed a significant difference between the two groups (p = 0.001 < 0.05). These findings indicate that the use of the Easy English YouTube channel had a significant effect on students’ vocabulary mastery.